THE ACCOUNTING EXCHANGE. - Littleton, A. C. (The Accounting Review, 1945)
Abstract The article presents information on the accounting exchange. Plans are being made that have much promise for bringing the American Institute of Accountants and the American Accounting Association into close cooperation for considering the educational problems of accountancy. Joint meetings are being planned to explore ways of finding and expressing ideas that may aid in the continued development of education for careers in accountancy. It is evident from the tentative agenda of topics for discussion, that plenty of useful work is waiting. Some of the topics for discussion are: (1) curricula for persons preparing for accountancy, (2) programs for the employment of college graduates best qualified for public accountancy, (3) desirable content for a pamphlet for the use of persons planning for careen in accounting. (4) preparation of an up-to-date bibliography of important books on accounting and its related fields of specialization, (5) policy to be followed by the Institute in meeting requests for recommendations as to schools in which to study accounting (6) programs of staff training and (7) plans for lectures by members of the Institute before student bodies.